2015
DOI: 10.5978/islsm.15-or-15
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of laser-assisted in-office bleaching and home bleaching on sound and demineralized enamel

Abstract: Aims: This study investigated the effectiveness of laser-assisted in-office bleaching and homebleaching in sound and demineralized enamel. Materials and Methods:The sample consisted of 120 freshly-extracted bovine incisors. Half of the specimens were stored in a demineralizing solution to induce white spot lesions. Following exposure to a tea solution for 7.5 days, the specimens were randomly assigned to 4 groups of 30 according to the type of enamel and the bleaching procedure employed. Groups 1 and 2 consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
0
23
0
5
Order By: Relevance
“…Our study had a significant increase in the lightness values (L*) and a decrease in the blueness (b*) and greenness (a*) values which directed the ∆E toward the lighter color scale indicating color improvement. 19 It is noteworthy to mention that although most of the stains (orange/brown) had a significant color improvement and were efficiently bleached, yet some stains (gray/black) bleached to a lesser extent. This variation in the color outcome (∆E 1.1-24.7) can be explained by the different stain history of the ACLs (chemical composition, type, and depth), associated with the variety of patients enrolled in the study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our study had a significant increase in the lightness values (L*) and a decrease in the blueness (b*) and greenness (a*) values which directed the ∆E toward the lighter color scale indicating color improvement. 19 It is noteworthy to mention that although most of the stains (orange/brown) had a significant color improvement and were efficiently bleached, yet some stains (gray/black) bleached to a lesser extent. This variation in the color outcome (∆E 1.1-24.7) can be explained by the different stain history of the ACLs (chemical composition, type, and depth), associated with the variety of patients enrolled in the study.…”
Section: Discussionmentioning
confidence: 98%
“…Our study had a significant increase in the lightness values ( L *) and a decrease in the blueness ( b *) and greenness ( a *) values which directed the ∆ E toward the lighter color scale indicating color improvement. 19 …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a mild hydrogen peroxide agent was added to NaHCO3 in order to evaluate whether 1.5% H2O2 increases the whitening effect of the resulting mixture. It is believed that the decomposition of hydrogen peroxide leads to the formation of hydroxyl, perhydroxyl or superoxide anion radicals, which degrade high-molecular pigments to achromic low-molecular substances, thus producing the whitening effect ( 8 , 23 , 24 ). This study found no significant difference in removing tooth stain between the agent containing sodium bicarbonate and that containing sodium bicarbonate + 1.5% H2O2.…”
Section: Discussionmentioning
confidence: 99%
“…The main materials used for dental bleaching are hydrogen peroxide for in-office bleaching and carbamide peroxide for at-home bleaching [11]. In-office bleaching utilizes a source of light or laser to activate the agent [12]. There are variable reports on the effectiveness of each of them depending on the concentration of the agent, application time, number of applications and the activating agent [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In-office bleaching utilizes a source of light or laser to activate the agent [12]. There are variable reports on the effectiveness of each of them depending on the concentration of the agent, application time, number of applications and the activating agent [12,13]. The use of other materials such as chlorine dioxide has also been reported [14].…”
Section: Introductionmentioning
confidence: 99%